FAKTOR-FAKTOR YANG MEMPENGARUHI TINGKAT PENGEMBALIAN INVESTASI PADA PERUSAHAAN MANUFAKTUR DI BEI - Ika Sari, Luthfi Nurmala; Priyadi, Maswar Patuh (Jurnal Ilmu dan Riset Akuntansi (JIRA), 2016)
The research is aimed to find out what sort of factor which influences the rate of return on investment inthe form of dividends. Investors want to find out the possibility to gain profit in the form of dividends frominvestment. The data is the secondary data that has been obtained from the annual report. The population is allmanufacturing companies which are listed in Indonesia Stock Exchange in 2011-2014 periods, the determinationof sample collection has been done by using purposive sampling and 120 companies have been selected assamples. This research has been carried out by using multiple linear regressions analysis and SPSS program.The result of the research indicates that NPM and DER have positive influence to the return on investment inthe form of dividend (DPR) whereas company growth which is measured by using sales growth has negativeinfluence to the return on investment in the form dividend. However, liquidity and firm size which is measuredby using CR and firm size does not have any influence to the rate of return on investment in the form ofdividend.Keyword: profitability, liquidity, leverage, growth, company size, dividend